A blind climber: The first evidence of ultrasonic echolocation in arboreal mammals. Issue 2 (March 2017) - PANYUTINA, Aleksandra A.; KUZNETSOV, Alexander N.; VOLODIN, Ilya A.; ABRAMOV, Alexei V.; SOLDATOVA, Irina B.
Abstract: The means of orientation is studied in the Vietnamese pygmy dormouse Typhlomys chapensis, a poorly known enigmatic semi‐fossorial semi‐arboreal rodent. Data on eye structure are presented, which prove that Typhlomys (translated as "the blind mouse") is incapable of object vision: the retina is folded and retains no more than 2500 ganglion cells in the focal plane, and the optic nerve is subject to gliosis. Hence, Typhlomys has no other means for rapid long‐range orientation among tree branches other than echolocation. Ultrasonic vocalization recordings at the frequency range of 50–100 kHz support this hypothesis. The vocalizations are represented by bouts of up to 7 more or less evenly‐spaced and uniform frequency‐modulated sweep‐like pulses in rapid succession. Structurally, these sweeps are similar to frequency‐modulated ultrasonic echolocation calls of some bat species, but they are too faint to be revealed with a common bat detector. When recording video simultaneously with the ultrasonic audio, a significantly greater pulse rate during locomotion compared to that of resting animals has been demonstrated. Our findings of locomotion‐associated ultrasonic vocalization in a fast‐climbing but weakly‐sighted small mammal ecotype add support to the "echolocation‐first theory" of pre‐flight origin of echolocation in bats.